Annual variation in reproductive parameters of Adélie penguins at Edmonson Point, Victoria Land, Antarctica - Pezzo, F.; Olmastroni, S.; Volpi, V.; Focardi, S. (Polar Biology, 2007)
Annual egg and chick production and breeding success at the Adélie penguin (Pygoscelis adeliae) colony Edmonson Point (74°21′S- 165°10′E), Victoria Land, is presented for eight breeding seasons between 1995 and 2005. During this period the colony consisted of 10-13 subcolonies and averaged 2098 ± 278 breeding pairs. A sample of over 100 nests (114-150), belonging to two subcolonies, was monitored each year. Some breeding parameters remained constant while others showed substantial annual variation. Laying date showed little variation, and laying was highly synchronous: 82.5% of clutches were initiated in a 10-day period, 9-18 November. In contrast, clutch size (1.77-1.97) and incubation period (34.4 ± 2.5) varied significantly. Variation among years was also recorded in hatching success (from 58 to 86%) and breeding success. This last parameter, measured as number of chicks reared to crèche per nest with eggs, varied between 0.34 and 0.97. © 2007 Springer-Verlag.